2002
DOI: 10.1097/00005110-200202000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Quality Outcome Indicators

Abstract: The purpose of this study was to assess the feasibility and conduct a pilot study of the ANA Nursing Care Report Card Study in one state. Clinical indicators studied include agency data, skin integrity, patient falls, and nurse (n = 217) and patient (n = 924) satisfaction. Patients were well satisfied with their care. Nurses were less satisfied, with a significant difference between what was important to their satisfaction and their current level of satisfaction. Important information is included for hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…A related publication about 181 patients with a history of falls refers to falls from bed (49%), while walking (43%) and falls from chair (8%) (8) . In another study, carried out during one year at 42 intensive nursing care units, 64 falls were reported, in which 80% of patients were walking alone or with help, while 20% were bedridden (7) . It is also mentioned that 30% of falls occur when patients get out of bed and go to the bathroom (9) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A related publication about 181 patients with a history of falls refers to falls from bed (49%), while walking (43%) and falls from chair (8%) (8) . In another study, carried out during one year at 42 intensive nursing care units, 64 falls were reported, in which 80% of patients were walking alone or with help, while 20% were bedridden (7) . It is also mentioned that 30% of falls occur when patients get out of bed and go to the bathroom (9) .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, knowing what patients face greater risks of falls, specific prevention and safety measures can be put in practice, so as to preserve patients' health and care quality (6) . A study in the United States found that only 4.8% of patients assessed without risk of falls upon admission actually fell during hospitalization (7) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations